Double crush syndrome: clinical review of an unsolved puzzle - Kuruwa, Deven R.; Elango, Easwar; Shah, Kunal A. (International Journal of Research in Orthopaedics, 2020)
Double crush syndrome (DCS) involves compression of a peripheral nerve at two different segments. Median nerve is most commonly involved with proximal compression at the level of cervical spine and distal compression in the carpal tunnel. Little consensus exists in literature regarding its epidemiology, risk factors, pathophysiology and definitive treatment. The purpose of this article is to summarize our current knowledge about this disease process as well as to touch upon the controversies that have been generated in recent times.